43.4k views
4 votes
Simplify the expression. Use the varbiables, numbers, and symbols that are shown. Drag them to the appropriate box in the polynomial. Use standard polynomial format. X(2x+3)+(x-3)(x-4)

User Sooth
by
5.1k points

2 Answers

4 votes

Answer:

f(x) = 3x^2 - 4x + 12

Explanation:

First, let's label the expression and do a little housekeeping:

X(2x+3)+(x-3)(x-4) should be f(x) = x(2x+3)+(x-3)(x-4).

If we perform the indicated multiplication, we get:

f(x) = 2x^2 + 3x + (x^2 - 7x + 12), or

f(x) = 2x^2 + 3x + x^2 - 7x + 12. Combine like terms to obtain:

f(x) = 3x^2 - 4x + 12

User Gerben Jacobs
by
5.1k points
3 votes

Answer:

3x² -4x +12

Explanation:

This involves straightforward application of the distributive property

x(2x+3)+(x-3)(x-4)

= 2x² +3x +x(x -4) -3(x -4)

= 2x² +3x +x² -4x -3x +12

= 3x² -4x +12

User Nick Banks
by
4.5k points